2012
DOI: 10.1002/ange.201108466
|View full text |Cite
|
Sign up to set email alerts
|

Organogold(III) Supramolecular Polymers for Anticancer Treatment

Abstract: Gold cures: The depicted gold(III) complex self‐assembles into supramolecular polymers which form nanofibrillar networks that display sustained cytotoxicity and can also act as carriers for other cytotoxic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…[6] In organic compounds, the noncovalent interactions used for gelation include p-p stacking interactions between aromatic rings, hydrophobic-hydrophobic interactions between long alkyl chains and hydrogen bonding between hydrogenbond donors and hydrogen-bond acceptors; the latter of which are also widely utilized in peptide-containing gelators. Besides organic gelators, metallogelators have also attracted much attention, [9][10][11][12][13][14][15][16][17] not only owing to their distinct luminescence [10,12,[13][14][15][16][17] and catalytic properties, [11] but also the possibility of making use of metal-metal interactions as an additional driving force for gelation. [13,15,16] Upon sol-gel transition, the metal-metal interactions will be interrupted, which could result in drastic spectroscopic changes.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In organic compounds, the noncovalent interactions used for gelation include p-p stacking interactions between aromatic rings, hydrophobic-hydrophobic interactions between long alkyl chains and hydrogen bonding between hydrogenbond donors and hydrogen-bond acceptors; the latter of which are also widely utilized in peptide-containing gelators. Besides organic gelators, metallogelators have also attracted much attention, [9][10][11][12][13][14][15][16][17] not only owing to their distinct luminescence [10,12,[13][14][15][16][17] and catalytic properties, [11] but also the possibility of making use of metal-metal interactions as an additional driving force for gelation. [13,15,16] Upon sol-gel transition, the metal-metal interactions will be interrupted, which could result in drastic spectroscopic changes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also showed that most metallopolymers were under thermodynamically changing processes with change of temperature ,,. Until now, many supramolecular metallopolymers of gold, copper and platinum complexes, have been well documented,,,, and the search for application potential has become new research focus.…”
Section: Figurementioning
confidence: 99%
“…To enhanceb ioavailability,b iological activity,a nd target specificity,t he uses of polymeric substances, such as biocompatible organic polymers, [14] heat-and pH-sensitive materials, [15] and some metal-based supramolecular polymers [16] to encapsulate and transport bioactive compounds or drugs have widely been reported. More recently,m etal-organic frameworks (MOFs), ac lass of porous materials with the advantages of high surface area and structural tunability,w ere employed to encapsulate various drugs and bioactive molecules.…”
mentioning
confidence: 99%
“…The cell viabilityineach lower chamber was hence determined by MTT assay. [16] As acontrol experiment, the time-dependence in the cytotoxicity of 1 at 8.7 mm was also examined over 72 h. Aliquots of 1 in DMSO/PBS solution was added to different sets of chambersc ontaining A2780cisc ells after 0, 24, 48, 64, 68, and7 0h,c orresponding to the cells that were incubated with 1 for7 2, 48, 24, 8, 4a nd 2h,r espectively.T he cell viability was determined at the total incubation time of 72 hbyM TT assay.…”
mentioning
confidence: 99%
See 1 more Smart Citation